Performance Evaluation - Annual Report Year 3 - Georg Buss; Nils Parasie; Daniel Veit; Michele Catalano; Pablo Chacin; Isaac Chao; Felix Freitag; Leandro Navarro; Omer F. Rana; Liviu Joita; Björn Schnizler; Werner Streitberger; et al. (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2007)
This report describes the work done and results obtained in third year of the CATNETS project. Experiments carried out with the different configurations of the prototype are reported and simulation results are evaluated with the CATNETS metrics framework. The applicability of the Catallactic approach as market model for service and resource allocation in application layer networks is assessed based on the results and experience gained both from the prototype development and simulations.
urn:nbn:de:bvb:703-opus-3746
Keywords: 330; Grid Computing